APLIKASI SENSOR WARNA TCS3200 PADA SISTEM PENYORTIRAN BARANG BERBASIS INTERNET OF THINGS (IOT) - Junaidi Burdadi; Ridwan R; Muhammad Iqbal Nugraha; Idra Dwisaputra (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The rapid development of technology in the industrial world applies the concepts of automation carried out by machines without using human power in the application of a system. There are many systems used to simplify human work, such as item code identifiers in the barcode process. In this journal the TCS3200 color sensor application is used as a medium to read the values ​​of four types of colors, including: red, blue, yellow and green. After the TCS3200 color sensor detects the color, the NodeMcu will process the data which will be grouped into 5 types using four servo motors as arms that function to enter items that have been identified by the TCS3200 color sensor according to their respective color containers. The TCS3200 color sensor is also used as a medium to calculate how many items of each color are detected and will be displayed on the IoT-based blynk application. This application can monitor how much of each color is in the container and can also control to start and stop the system. This test was carried out 9 times and there were no errors in the test and the number that was read on the blynk application and the manual system was the same.